The efficacy of a nitric oxide-releasing formulation on nares isolated Methicillin-Resistant Staphylococcus aureus in porcine wound infection model - Davis, Stephen C.; Gil, Joel; Solis, Michael; Strong, Ryan (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe colonization of Staphylococcus aureus (SA) acquired in nosocomial infections may develop acute and chronic infections such as Methicillin-Resistant Staphylococcus aureus (MRSA) in the nose. As a commensal microorganism with the ability to form a biofilm, SA can dwell on the skin, nostrils, throat, perineum, and axillae of healthy humans. Nitric oxide (NO) is an unstable gas with various molecular functions and has antimicrobial properties which are converted into many potential treatments.MethodsMethicillin-Resistant Staphylococcus aureus MRSA BAA1686 isolated from nasal infection was used in a porcine wound infection model. Deep partial-thickness wounds (10mm x 7mm x 0.5mm) were made on three animals using a specialized electrokeratome. All wounds were inoculated and then covered with polyurethane film dressings for biofilm formation. After 48 hours, three wounds were recovered from each animal for baseline enumeration. The remaining wounds were randomly assigned to six treatment groups and treated once daily. The treatment groups are as follows: NO topical ointments concentrations of 0.3, 0.9 and 1.8%, Vehicle Ointment, Mupirocin 2%, and Untreated Control. Microbiological recoveries were conducted on day 4 and day 7.ResultsThe greatest efficacy observed from the NO formulations against MRSA BAA1686 was the 1.8% concentration. This agent was able to reduce more than 99% of bacterial counts when compared to Baseline, Vehicle Ointment, and Untreated Control wounds on both assessment days. Mupirocin 2% was the overall best treatment against MRSA BAA1686 on both assessment days, with a significant reduction (p ≤ 0.05) of 4.70 ± 0.13 Log CFU/mL from day 4 to day 7.ConclusionsOverall, the positive control Mupirocin 2% was the most effective in eliminating MRSA BAA1686 throughout the study. This experiment demonstrated a downward trend from the highest concentration of NO topical ointment formulations to the lowest concentrations on both assessment days (0.3% - 1.8%). Out of all NO topical ointments, the highest concentration (1.8%) was the most effective with the potential to be an alternative treatment against a MRSA nasal strain biofilm.